Significance of Sonographic Characterization and FNAC of Small Size Thyroid Nodules (Medical Forum Monthly, 2024)
Objective: The purpose of this study is to determine the accuracy of various ultrasound characteristics of small size thyroid nodules in the predication of malagnancy and the usefullness of ultrasound guided FNAC of these nodules.Study Design: Experimental study. .Materials and Methods: This study was conducted on 70 patients, in whom 76 thyroid nodules 4mm to 10mm in size were biopsied. Diagnostic ultrasound was performed with high frequency linear probe for the evaluation of following ultrasound characteristics, internal structure, echogenicity, margins, posterior acoustic shadowing, height to width ratio, halo around the nodules, calcifications and vascular flow on Doppler scan. Each character was corelated with the results of FNAC to determine the accuracy of the feature in the prediction of malagnancy.Results: Out of 76 FNACs of 4mm to 10mm size thyroid nodules 8(10.5%) biopsies did not yeild significant cytological specimen. Another 8(10.5%) specimen were classified as indeterminate so no further analysis was done. The rate of malignancy among nodules on final diagnosis was 20%. The most accurate sonographic features associated with malignancy were posterior acoustic shadowing (88.3%), taller than wider (83%), Halo around the nodule (80%) and calcification (70%). Conclusion: Small size thyroid nodules are associated with significant risk of malagnancy. Certain sonographic characteristics can be used to measure the risk of malagnancy. FNAC of these nodules can be safely and accurately performed with high diagnostic rate.